Features of obsessive and pseudoobsessive symptoms in patients with OCD and in patients with schizophrenia spectrum disorders - Grynevych Євгенія (Psychosomatic Medicine and General Practice, 2025)
Relevance. Obsessions and compulsions are the most striking manifestations of non-psychotic mental pathology, which lead to a significant decrease in the quality of life and in some cases can lead to patients` complete disability. Obsessive-compulsive symptoms, like other symptoms of mental pathology, undergo pathomorphosis over time. The study of the features of obsessive and pseudoobsessional symptoms in schizophrenia spectrum disorders and in OCD creates a basis for understanding the current state of obsessions in various mental pathologies and for updating modern criteria for differential diagnosis of obsessions and pseudoobsessions. Aim. Identify the features of obsessive and pseudoobsessive symptoms in patients with OCD and in patients with schizophrenia spectrum disorders. Materials and methods. 42 patients with schizophrenia spectrum disorders and manifestations of pseudoobsessive symptoms and ritualized behavior, as well as 50 patients with OCD, were examined. Features of obsessive, compulsive, and pseudoobsessive symptoms and ritualized behavior, such as their thematic representation and severity, were determined using the Yale-Brown Obsessive Compulsive Disorder Scale (Y-BOCS). Results. The study found that the themes of obsessive and pseudoobsessive symptoms did not demonstrate statistically significant differences. However, it was found that repetitive rituals were significantly more common in the group of people with schizophrenia spectrum disorders, and checking compulsions were more common in the group of people with OCD. The intensity of obsessive-compulsive symptoms was significantly higher in the group of individuals with OCD, which is explained by the lack of affective saturation, and therefore the painfulness of experiences caused by pseudo-obsessive and pseudo-compulsive symptoms in individuals with schizophrenia spectrum disorders.